The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/advs.202304871
|View full text |Cite
|
Sign up to set email alerts
|

Kirigami‐Structured, Low‐Impedance, and Skin‐Conformal Electronics for Long‐Term Biopotential Monitoring and Human–Machine Interfaces

Meili Xia,
Jianwen Liu,
Beom Jin Kim
et al.

Abstract: Epidermal dry electrodes with high skin‐compliant stretchability, low bioelectric interfacial impedance, and long‐term reliability are crucial for biopotential signal recording and human–machine interaction. However, incorporating these essential characteristics into dry electrodes remains a challenge. Here, a skin‐conformal dry electrode is developed by encapsulating kirigami‐structured poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)/polyvinyl alcohol (PVA)/silver nanowires (Ag NWs) film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…41 Furthermore, Xia et al demonstrated kirigamistructured epidermal electrodes composed of PEDOT:PSS/ polyvinyl alcohol(PVA)/Ag NWs/polyurethane, featuring high stretchability, low interfacial impedance, and skin conformity. 42 Although these electrodes can conform well to human skin under various deformations and are utilized as stretchable epidermal electrodes, the absence of self-healing capabilities may render the electrodes susceptible to damage during utilization, particularly when subjected to stressful conditions such as severe compression, torsion, or stretching. Such conditions can significantly compromise the longevity of the electrode, thereby limiting its overall performance and durability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…41 Furthermore, Xia et al demonstrated kirigamistructured epidermal electrodes composed of PEDOT:PSS/ polyvinyl alcohol(PVA)/Ag NWs/polyurethane, featuring high stretchability, low interfacial impedance, and skin conformity. 42 Although these electrodes can conform well to human skin under various deformations and are utilized as stretchable epidermal electrodes, the absence of self-healing capabilities may render the electrodes susceptible to damage during utilization, particularly when subjected to stressful conditions such as severe compression, torsion, or stretching. Such conditions can significantly compromise the longevity of the electrode, thereby limiting its overall performance and durability.…”
Section: ■ Introductionmentioning
confidence: 99%